The Influence of New Ventures' Work Environment and Innovation Behaviors on Corporate Performance - Xiang, Yonghui; Wang, Weiwei (Frontiers in Psychology, 2022)
The purpose of the study is to improve the business performance of new ventures. The influence of working environment and innovation behaviour on business performance based on personality psychology is studied. First, the relevant theories of new ventures are introduced, and then the structural equation model is displayed. Second, the conceptual model is constructed in response to the two influencing factors of new ventures. Finally, the influencing factors of new venture performance are extracted according to the conceptual model, and a questionnaire is designed. Statistical Product and Service Solutions software is used to analyze the questionnaire data. The results show that the proportion of new enterprise developers is from 8%-16%, and the number of employees is less than 150 people. The establishment time of the surveyed enterprises is from 3 to 7 years, and the proportion of the enterprises whose establishment time is less than 3 years is 30.79%. Management means policies, exploratory innovation, and applicability innovation have different effects on the business performance of new ventures. Among them, the management means of managers have the greatest impact on business performance, accounting for 32.57%, followed by the applicability innovation behaviour of employees, accounting for 29.47%; the exploratory innovation behaviour of employees takes up 26.47%. The policy environment in the industry where the enterprise is located has the smallest impact on business performance. The results of the hypotheses show that exploratory innovation and applicability innovation do not influence each other; working environment and innovation behaviour have a great influence on the performance of enterprises; the most influential factor is the management means of managers. This study provides a reference for new ventures to improve their performance based on the working environment and innovation behaviour.